Process intensification of ozonolysis reactions using dedicated microstructured reactors. Issue 12 (10th September 2021) - Polterauer, Dominik; Roberge, Dominique M.; Hanselmann, Paul; Elsner, Petteri; Hone, Christopher A.; Kappe, C. Oliver
Abstract : A dedicated microreactor system ensures exquisite control over mass and heat transfer for performing very fast ozonolysis. Abstract : Ozonolysis reactions are generally high-yielding, highly selective, and sustainable processes, especially when performed in green solvents. However, ozonolysis is underutilized in organic synthesis and chemical manufacture due to the safety concerns associated with handling ozone (O3 ) gas and the highly reactive ozonide intermediate. In this article, the development of ozonolysis reactions within a dedicated microreactor platform suitable for gas–liquid transformations is described. The optimization of the reaction conditions for the ozonolysis of cyclohexene to hexanedial, and thioanisole to methyl phenyl sulfoxide is presented. Cyclohexene is transformed to hexanedial in 94% yield at 0 °C within 1.7 seconds. In a similar fashion, the ozonolysis of thioanisole was achieved in 99% yield at 0 °C within <1 second. A 3D printed heat flow calorimeter was used to measure the heat of reaction for the ozonolysis of thioanisole, giving a value of −165 ± 4 kJ mol −1 . A 3 hour long run achieved a throughput of 1.77 g h −1 for methyl phenyl sulfoxide, which corresponds to a space time yield of 1.84 kg L −1 h −1 for this intensified process.